Assessment of the Health Status of the Oldest Olds Living on the Greek Island of Ikaria: A Population Based-Study in a Blue Zone. (30th November 2019) - Legrand, Romain; Manckoundia, Patrick; Nuemi, Gilles; Poulain, Michel
Abstract : Objective . To describe the demographic characteristics, socio-economic status, functional status (autonomy, strength), and health status (cognitive and thymic functions, cardiovascular risk factors, and nutritional status) of the oldest olds living on the Greek island of Ikaria. We also try to explain the longevity observed in this population. Methods . A cross-sectional observational study of people aged 90 and over living in both municipalities of north-western Ikaria (Evdilos and Raches) was conducted over one year, from October 21, 2012 to October 21, 2013. The participants were interviewed (medical history), had a brief clinical examination, and underwent standardized geriatric assessments including the Geriatric Depression Scale (GDS-15), the Mini-Mental-State Examination (MMSE), the Activities of Daily Living (ADL), the Instrumental ADL (IADL), and an assessment of grip strength. Results . Seventy-one persons (37 females, 34 males), aged 94.1 years on average, were interviewed at their homes. Seven percent were current smokers (females 5.4%, males 8.8%). Hypertension was diagnosed in 70.4% of participants, diabetes in 19.7%, hypercholesterolemia in 12.7%, and obesity in 17.2%; 66.0% of the population had one chronic disease or more. The mean score for the GDS-15 scale was 3.7/15.0, 23.7/30.0 for the MMSE, 4.0/6.0 for the ADL, and 4.2/8.0 in females and 3.6/5.0 in males for the IADL. Grip strength was 17.0 kg in females and 26.5 kg in males. Conclusions . This study provides an overview of the socio-demographic and medical characteristics of the oldest olds living in a longevity Blue Zone.